(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
This paper seeks to study aspects of judicial activism in civil procedure. In particular, in the acquisition of evidence, in procedural cooperation, burden of proof, and the dynamic theory of burden of proof. Thus, despite the tendencies that devalue the growing protagonism of the activity of the civil judge, there are aspects where its is evident the increase of powers and protagonism of this procedural subject.